Pengaruh Peringkat Obligasi terhadap Keputusan Investasi, Tatakelola Perusahaan, dan Nilai Perusahaan (Studi pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di BEI Periode 2016-2020) - Almira Devina; Yulia Efni; Fitri Fitri (Program Studi Manajemen FEBM UMRAH, 2023)
This study aims to determine the effect of bond ratings on investment decisions, corporate governance, and firm value in the property and real estate sectors listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The population in this study amounted to 78 companies, but after selecting the sample using purposive sampling technique, a sample of 12 companies was obtained. Secondary data was obtained from the IDX's official website, fact books, company's official website, and PEFINDO. Hypothesis testing was carried out by path analysis and Sobel test using the WarpPLS 5.0 program. The results of this study indicate that the bond rating has a significant positive effect on investment decisions. Bond rating has a significant positive effect on corporate governance. Bond rating has no significant positive effect on firm value. Investment decisions have a significant positive effect on firm value. Corporate governance has a significant negative effect on firm value. Bond rating has an indirect positive and insignificant effect on firm value through investment decisions as an intervening variable. Bond rating has a significant negative indirect effect on firm value through corporate governance as an intervening variable.